Wilkinson, D. (2013): Death or Disability? The ‘Carmentis Machine’ and Decision-making for critically ill children. Oxford: Oxford University Press. - Arruabarrena Ubetagoyena, Ane (Revista Española de Discapacidad, 2013)
Reseña de la obra ’Death or Disability? The ‘Carmentis Machine’ and Decision-making for critically ill children’ (2013) de Dominic Wilkinson.